Teens, power tools, and green schools: Education for sustainability through a university environmental design program and middle school partnership. Issue 3 (3rd July 2017) - Derr, Victoria
ABSTRACT: This article explores the role of green schools in promoting education for sustainability by reflecting on a university–middle school partnership focused on sustainable design. Undergraduates and middle school students met weekly for a semester to learn about sustainability through simple design projects and activities that focused on sustainability features of the school. Instructor and university student reflections explore the value and challenges in integrating education for sustainability and green schools that teach.